Differences in Work Engagement Between Civil Servants, Private Employees, Indonesian National Armed Forces And Employees Under Military Foundations - Dian Juliarti Bantam (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study aims to determine differences in work engagement between Civil Servants, Indonesian National Armed Forces, Private Employees and Employees under the Military Foundation. Work engagement is a positive state of mind and feeling that directs an employee's actions to solve problems or tasks within the scope of his work optimally and is characterized by enthusiasm (vigor), dedication (dedication), and absorption of work (absorption). In revealing the work engagement of research subjects, the Utrecht Work Engagement Scale 9 version (UWES-9) from Scaufeli and Baker was used which was adapted by Kristiana, Fajrianthi, and Purwono (2018). Analysis using Non-Parametric Kruskal Walling test. The results showed that there was no difference in work engagement between Civil Servants, Indonesian National Armed Forces, Private Employees and Employees under the Military Foundation (p = 0.187; p > 0.05). The mean rank for civil servants is 30.75, the mean rank for private employees is 44.21, the mean rank for employees under the military foundation is 47.29, and the mean rank for the military is 48.43. Based on the mean rank value for the profession category, it can be seen that the TNI has higher work engagement than other professional categories, and civil servants have lower work engagement than the other three. In general, the data shows that work engagement in these professions is in the 'High' category (43.02%; N=86).